Polycaprolactone/Doped Bioactive Glass Composite Scaffolds for Bone Regeneration - Ana Sofia Pádua; Manuel Pedro Fernandes Graça; Jorge Carvalho Silva (Journal of Functional Biomaterials, 2025)
Critical-size bone defects do not heal spontaneously and require external support, making bone regeneration a central challenge in tissue engineering. Polymeric/ceramic composite scaffolds offer a promising approach to mimic the structural and biological properties of bone. In this study, we aimed to evaluate the effect of different doping oxides in bioactive glass (BG) on the performance of polycaprolactone (PCL)-based composite scaffolds for bone tissue engineering applications. Composite scaffolds were fabricated using solvent casting, hot pressing, and salt-leaching techniques, combining PCL with 25 wt% of BG or doped BG containing 4 mol% of tantalum, zinc, magnesium, or niobium oxides, and 1 mol% of copper oxide. The scaffolds were characterized in terms of morphology, mechanical properties, and in vitro biological performance. All scaffolds exhibited a highly porous, interconnected structure. Mechanical compression tests indicated that elastic modulus increased with ceramic content, while doping had no measurable effect. Cytotoxicity assays confirmed biocompatibility across all scaffolds. Among the tested materials, the Zn-doped BG/PCL scaffold uniquely supported cell adhesion and proliferation and significantly enhanced alkaline phosphatase (ALP) activity—an early marker of osteogenic differentiation—alongside the Nb-doped scaffold. These results highlight the Zn-doped BG/PCL composite as a promising candidate for bone regeneration applications.